Collection development policy for the Child's Place Multiple Intelligence International School Foundation - Vergara, Marvin M. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Child's Place Multiple Intelligence International School Library has no written collection development policy that guides it in selecting and acquiring materials for the library's collection. This study shall create a written collection development policy that would suitably tailor to the information and curricular needs of Child's Place-Multiple Intelligence International School Library and its patrons. The objectives of the study are the following: 1) to come up with a written collection development policy in line with the mission and vision of the school; and 2) to ascertain the needs of the patrons of the library.